Monitoring sociodemographic inequality in COVID-19 vaccination uptake in England: a national linked data study. Issue 7 (25th April 2022) - Dolby, Ted; Finning, Katie; Baker, Allan; Fowler-Dowd, Leigh; Khunti, Kamlesh; Razieh, Cameron; Yates, Thomas; Nafilyan, Vahe
Abstract : Background: The UK began an ambitious COVID-19 vaccination programme on 8 December 2020. This study describes variation in vaccination uptake by sociodemographic characteristics between December 2020 and August 2021. Methods: Using population-level administrative records linked to the 2011 Census, we estimated monthly first dose vaccination rates by age group and sociodemographic characteristics among adults aged 18 years or over in England. We also present a tool to display the results interactively. Results: Our sample included 35 223 466 adults. A lower percentage of males than females were vaccinated in the young and middle age groups (18–59 years) but not in the older age groups. Vaccination rates were highest among individuals of White British and Indian ethnic backgrounds and lowest among Black Africans (aged ≥80 years) and Black Caribbeans (18–79 years). Differences by ethnic group emerged as soon as vaccination roll-out commenced and widened over time. Vaccination rates were also lower among individuals who identified as Muslim, lived in more deprived areas, reported having a disability, did not speak English as their main language, lived in rented housing, belonged to a lower socioeconomic group, and had fewer qualifications. Conclusion: We found inequalities in COVID-19 vaccination uptake rates by sex, ethnicity, religion, area deprivation, disability status, English language proficiency, socioeconomic position and educational attainment, but some of these differences varied by age group. Research is urgently needed to understand why these inequalities exist and how they can be addressed.